A critical edition of two Bheki Mseleku Albums: transcribing Celebration and Timelessness - Cousins, David Somerset (My University, 2021)
This critical edition explores the music of Bheki Mseleku, an iconic South African jazz composer and multi-instrumentalist, through the transcription and analysis of his recordings. While Mseleku has occupied a peripheral space within the South African jazz landscape in comparison to more prominent, internationally recognised stars like Hugh Masekela and Abdullah Ibrahim, recent attention in the form of tribute concerts and scholarly research have highlighted his importance to South African jazz. My contribution takes the form of a critical edition centered around ‘lead sheet’ depictions of all nineteen compositions from his first two ensemble albums, Celebration (1992) and Timelessness (1994). Although jazz, as an orally transmitted art form, has recordings as its primary texts, western academic endeavour has traditionally prioritised written source material as essential for the transmission of research. Therefore, without accurate scores of Mseleku’s music available, I had to transcribe relevant recordings into notated form. Thus, transcription theory and practice occupy an important position within the research, especially with regards ‘descriptive’ versus ‘prescriptive’ visual depictions of Mseleku’s music. An analysis of Mseleku’s compositional, improvisatory and pianistic techniques as compared to his four main American jazz influences is based around these transcribed scores
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Music ,2020